The effects of simulated transport on the muscle characteristics of white-feathered end-of-cycle hens - C. Frerichs; K. Beaulac; T.G. Crowe; K. Schwean-Lardner (Poultry Science, 2021)
ABSTRACT: Transportation of end-of-cycle hens (EOCH) may result in birds’ experiencing metabolic stress, which changes muscle characteristics. This study evaluated the impacts of simulated transport on muscle characteristics of white-feathered EOCH (65–70 wk). The factorial arrangement included treatments of T/RH (-10°C uncontrolled RH [-10], 21°C with 30 [21/30] or 80% RH [21/80], 30°C with 30 [30/30] or 80% RH [30/80]), duration (4, 8, 12 h), and feather cover (105 well-feathered [WF], 105 poorly-feathered [PF]). A total of 210 hens/replicate/farm (farm=block; 3 total) were tested during the simulated transport. Crates (one/duration/replicate), divided in half for each feather cover (seven hens/side), were placed in a climate-controlled chamber. Prior to exposure, hens were fasted (6 h). BW was taken pre- and post-exposure, and the difference was calculated as live shrink. Post-exposure to the test conditions, birds were slaughtered and carcasses were analyzed for muscle characteristics. Data were analyzed as a randomized complete block design (farm of origin as block) with ANOVA (Proc Mixed, SAS 9.4; significance declared at P ≤ 0.05). Duration resulted in more weight loss for the birds (P < 0.01). Final pH measures (30 h post-mortem) were higher in hens exposed to -10 than 21/80, 30/30, and 30/80 and this difference was exacerbated with time (breast P < 0.01 and thigh P = 0.01). For muscle color, breast and thigh (both feather covers; P = 0.01) were darker in the -10 treatment while redness values were higher in EOCH exposed to this treatment (breast and thigh P < 0.01). Additionally, thigh muscle redness was higher in PF hens (P < 0.01). Thaw and cooking losses were impacted by T/RH and duration (thaw loss P = 0.03 and cook loss P = 0.04). Cook loss was also influenced by T/RH and feather cover with PF hen muscles losing less water during cooking in the -10 treatment (P = 0.01). Overall, the largest impact from transport was found in hens exposed for a longer duration to -10 antemortem compared to other treatments, demonstrating a significant impact on muscle characteristics from ante-mortem stress.